1975
DOI: 10.1159/000240777
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Volume Curves of Lamb Lungs and the Lecithin-Sphingomyelin Ratios of Lung Fluid

Abstract: Pressure-volume curves were made of lungs from non-distressed, from asphyxiated and from distressed lambs. The curves of the non-distressed animals differed from the curves of the asphyxiated and of the distressed group. Eleven stability indices were calculated and the summation of these in situ surfactant characteristics was used for individual respiratory distress syndrome diagnosis. Low values (< 2) of lecithin/sphingomyelin (L/S) ratios in lung fluid were found before the 130th day of gestation, but a stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Crosses shown in figure la represent the L/S ratios of six lambs from a previous study (9). No differences are noticed between these values and the L/S ratios from the present study.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Crosses shown in figure la represent the L/S ratios of six lambs from a previous study (9). No differences are noticed between these values and the L/S ratios from the present study.…”
Section: Resultssupporting
confidence: 52%
“…Volumes of 5 cm3 were used for the determination of the L/S ratio according to Gluck and Kulovich (12). The technics of phospholipid extraction and measurements have been reported previously (9). Briefly, lipids were extracted with chloroform methanol (2:1 v/v), the chloroform layer was dried under nitrogen and cold acetone was added to precipitate surface-active lecithin.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiovascular and pulmonary function data in pretemi lambs of less than 130 days gesta tion is remarkably sparse (4,10). The in vitro pulmonary surfactant studies on lamb fetuses by Brumfey et al (1) indicated that the preterm lamb of less than 120 days gestation, because of lack of surfactant, would require assisted venti lation for survival, and that the lungs of animals older than 130 days would behave like mature lungs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies on the ef fects of glucocorticoids on the biochemical maturation and mechanics of fetal lamb lungs (2,4,9). However, to our knowledge, evalua tion of postnatal pulmonary function and hemodynamic studies on preterm lambs pre treated with steroids have not been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation